Incidence and Risk Factors of Cholestasis in Newborns with Hemolytic Disease—A Case-Control Study - Drozdowska-Szymczak, Agnieszka; Mazanowska, Natalia; Pomianek, Tomasz; Ludwin, Artur; Krajewski, Paweł (Journal of clinical medicine, 2024)
Background/Objectives: One of the rare causes of cholestasis may be hemolytic disease of the fetus and newborn (HDFN). Methods: We retrospectively analyzed 88 medical records of HDFN newborns with cholestasis and 186 records of children with HDFN without cholestasis and conducted an observational, case-control, retrospective study. Results: Factors influencing the risk of cholestasis were lower gestational age at birth (36.83 ± 1.9 vs. 37.57 ± 1.8, p = 0.002), Rh or Kidd HDFN (80.7% vs. 53.2%), and the need for intrauterine transfusion (27.3 vs. 11.8%). The subjects had lower hemoglobin concentrations at birth (14.01 ± 3.8 vs. 16.39 ± 2.8 g/dL) and during whole hospital stay, higher cord blood total bilirubin concentration (4.26 ± 1.8 vs. 2.39 ± 1.4 mg/dL), higher maximum bilirubin concentration (15.27 ± 5.8 vs. 10.24 ± 3.4 mg/dL), and more frequent liver ultrasound abnormalities (19.9 vs. 6.3%). They also required more extended hospitalization due to higher rates of postnatal blood transfusion (33 vs. 3.8%), more frequent need for exchange transfusion (8.8% vs. 2.2%), more extended time and higher risk of phototherapy (94.3 vs. 59.1%), and higher usage of immunoglobulins (55.7 vs. 8.1%), parenteral nutrition (45.5 vs. 12.9%), and antibiotics (14.8 vs. 4.8%). Conclusions: The risk factors for cholestasis in children with HDFN are lower gestational age at delivery, Rh and Kidd serological type of HDFN, and the need for intrauterine transfusions.